2021
DOI: 10.9778/cmajo.20200025
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of faxed referrals and eConsult questions for rheumatology referrals: a descriptive study

Abstract: he number of patients requiring care from a rheumatologist has increased in recent years, while the number of rheumatologists available to provide clinical care remains inadequate and static. [1][2][3] In Canada, studies have found substantial variability in wait times for rheumatology. A study assessing time to first rheumatologist visit in new rheumatoid arthritis reported a mean wait time of 77 days, with a median wait time of 50 days. 4 Another study reported a mean wait time of 155 (standard deviation 88)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…eConsult services are an asynchronous web or electronic health record-based system consultation in which a referring provider can securely share health information with a subspecialist who can offer clinical advice without directly seeing the patient [50 ▪ ]. These programs hold the potential to provide more timely rheumatology consultative services for underserved rural patients [50 ▪ ,51 ▪ ]. eConsult services may allow primary care providers to solicit advice or answers to questions as an alternative to a face-to-face specialist referral, which avoids prolonged wait time, or provide basic recommendations to support patients awaiting in-person evaluation [50 ▪ ,51 ▪ ,52].…”
Section: Telemedicine and Telehealth Strategies To Improve Care Deliv...mentioning
confidence: 99%
See 1 more Smart Citation
“…eConsult services are an asynchronous web or electronic health record-based system consultation in which a referring provider can securely share health information with a subspecialist who can offer clinical advice without directly seeing the patient [50 ▪ ]. These programs hold the potential to provide more timely rheumatology consultative services for underserved rural patients [50 ▪ ,51 ▪ ]. eConsult services may allow primary care providers to solicit advice or answers to questions as an alternative to a face-to-face specialist referral, which avoids prolonged wait time, or provide basic recommendations to support patients awaiting in-person evaluation [50 ▪ ,51 ▪ ,52].…”
Section: Telemedicine and Telehealth Strategies To Improve Care Deliv...mentioning
confidence: 99%
“…In a descriptive study, rheumatologists agreed that eConsults have the potential to address specific questions (e.g. drug-related questions, or questions about diagnosis, management, or procedures) that otherwise would become routine consultations [51 ▪ ].…”
Section: Telemedicine and Telehealth Strategies To Improve Care Deliv...mentioning
confidence: 99%
“…In many cases, these patients do not require any additional workup or treatment, raising concern that PCPs are uncertain about diagnosis or management even in these less acute common conditions. Studies in other specialties have shown that many of traditional referrals can be converted to e-consults, 5,12 which is also true for pediatric neurology. Further discussion and targeted education with PCPs may lead to changes in practice regarding which clinical problems are appropriate for e-consults.…”
Section: Discussionmentioning
confidence: 99%
“…Patient ages varied from neonates to 19 years old with a mean age of 8.7 years (SD = 6.0) and a median age [IQR] = 9 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Of these, 20.6% (N = 12) were ≤ age 1 year.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation